Polite Girls and Creative Boys? Students' Gender Moderates Accuracy of Teachers' Ratings of Creativity. (December 2013) - Gralewski, Jacek; Karwowski, Maciej
Abstract The aim of this study was to examine whether, and to what extent, teachers are able to recognize the creativity of their students. The study measured the creative abilities, creative attitude, creative activity, as well as intrinsic motivation, intelligence, and school functioning of 589 Polish high school students, while their teachers (N = 178) rated students' creativity. The structural equation model (SEM) demonstrated that the accuracy of teachers' ratings of students' creativity is generally low—the latent factor of students' creativity reliably, however weakly, predicted teachers' ratings. The accuracy of teachers' ratings was moderated by gender: Only in the case of male students did the latent creativity factor reliably predict teachers' ratings. Students' school functioning emerged as a key factor positively associated with the perception of students as creative.